2019
DOI: 10.1002/cplu.201800660
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of 4‐Aminophenol Molecules at the Surface of an FeS2/Carbon Nanotube Modified Glassy Carbon Electrode in Aqueous Medium

Abstract: FeS2/carbon nanotube (CNT) nanocomposites were synthesized and immobilized on the surface of a glassy carbon electrode (GCE) in order to investigate the electrocatalytic conversion of 4‐aminophenol (4‐AP) into p‐quinone in an aqueous medium. The reformed electronic properties (in terms of lowering of band‐gap energy and charge‐transfer resistance), as well as improved surface area, result in an enhanced redox reaction of 4‐AP in the presence of FeS2‐CNT NCs compared to that with FeS2 alone. The 4‐AP molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 60 publications
4
21
0
Order By: Relevance
“…Therefore, it is observed that BaO NRs/GCE has higher ability to transfer the charges in an electrochemical oxidation/reduction reaction. The similar observation has been reported in the identical conditions elsewhere [52,53] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is observed that BaO NRs/GCE has higher ability to transfer the charges in an electrochemical oxidation/reduction reaction. The similar observation has been reported in the identical conditions elsewhere [52,53] …”
Section: Resultssupporting
confidence: 91%
“…The similar observation has been reported in the identical conditions elsewhere. [52,53] Figure 4(a) is shown in below about the scan rate (SR) of BaO NRs/GCE in 0.1 mM Fe(CN) 6 3À /4À by using cyclic voltammetric approach in a phosphate buffer medium at pH 7.0. The oxidation and reduction peaks are found at + 0.38 V and + 0.12 V respectively in 0.1 mM Fe(CN) 6 3À /4À , which are linearly shifted in a range of SR (50.0~325.0 mV/s) (Figure 4a).…”
Section: Electrochemical Characterization Of Modified Gcementioning
confidence: 99%
“…It has the less charge‐transfer resistance ( R ct ) compared to the bare GCE. Therefore, it can be concluded that the ZnO‐doped Co 3 O 4 NPs modified GCE has more ability to transfer the charges during electrochemical oxidation/reduction reaction as reported elsewhere [43,44] …”
Section: Resultssupporting
confidence: 67%
“…We expect faster electron mobility on the PDA/PPY modified GCE, if the synthesis of PDA/PPY was successful. In EIS, the diameter of the semicircle denotes the charge‐transfer resistance (R ct ) at the surface of the electrode . As presented in Fig 4(a), the bare GCE displayed an increased R ct diameter compared to the PDA/PPY modified GCE in a solution containing 0.1 M PBS and 0.5 mM UA.…”
Section: Resultsmentioning
confidence: 99%